The Effect of Money Ethic on Tax Evasion with Religiosity, Materialism, and Gender as Moderating Variables - Wardani, Dewi Kusuma; Subekti, Merlin (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2023)
This study aims to examine the effect of money ethics on tax evasion whit religiosity, materialism, and gender as moderating variabels. This research method uses quantitative descriptive methods and primary data using a questionnaire. The study took a samples of individual taxpayers (WPOP). The sampling technique uses incidental sampling. Data collection was carried out by leaving questionnaires in the form of google forms and questionnaires. The number of questionnaires that were processed was 120 questionnaires. Data analysis used in this study is a moderated regresion analysis whit an absolute difference test. The results showed that money ethics has a possitive effect on tax evasion. Intrinsic religiosity weakend the positive relationship between money ethics and tax evasion. Extrinsic religiosity, materialism aand gender strengthen the positive relationship between money ethics and tax evasion.